Challenges and Sustainable Development of Small And Medium-sized Enterprises: Evidence from a Local Processing Company in Ghana (Nkulenu). - APHU, ELVIS SELASE; ADATOR, STEPHANIE WORLANYO (Advances in Social Sciences Research Journal, 2018)
Small and Medium-sized Enterprises (SMEs) have been shown by several studies which perform significant roles in economic growth and development worldwide. As often described, SMEs serve as efficient and profitable job creators as well as the seeds for big businesses and the fuel for engines of national economy. Even in the developed countries, SMEs Sector has been one of the largest employers. Interest in the role of SMEs in the developmental process continues to be in the lead of policy debates in most countries. Governments at all levels have undertaken initiatives to promote the growth of SMEs (Carsamer, 2009; Feeney and Riding, 1997).